The relevance of motivation in schizophrenia - Paulet Manuel; Ciobica Alin; Cojocaru Sabina; Popescu Radu; Timofte Daniel (Archives of Biological Sciences, 2015)
Lately there is a growing interest in the negative symptoms in schizophrenia and their mechanisms of action, with special focus on the motivation process. The lack of motivation is increasingly recognized to be a very important impediment to positive management in schizophrenic pathology. In this mini-review, we described the current understanding of the nature and causes of the specific motivational deficits in schizophrenia in order to find better management strategies for this heterogeneous disorder. All the data and theories presented here clearly demonstrate that amotivation is a fundamental aspect of the negative symptomatology in schizophrenia and could represent a useful factor in understanding and improving the mechanisms and further management of schizophrenia.